Menopause, aging and the failing pelvic floor: a clinician's view. (2nd November 2021) - Caretto, M.; Misasi, G.; Giannini, A.; Russo, E.; Simoncini, T.
Abstract: The management of pelvic organ disorders is common and challenging work. Nowadays, midlife women are more active than they were in the past, and the development of pelvic organ prolapse (POP) disrupts quality of life and impairs social and personal activities. The aging process and hormonal changes have a role in influencing the structure and function of the lower urinary and genital tract. Correct diagnosis of pelvic organ disorders and the identification of women's symptoms are the hallmarks of tailored management. Treatment is multimodal and multidisciplinary; it requires competence in pelvic medicine and surgery. When conservative treatments fail, women with symptomatic POP are candidates for reconstructive surgery: the optimal management requires clinicians who are familiar with all of the available strategies and who are able to choose the best strategies in a tailored manner. Knowing and understanding the management of POP should be integrated into the practice of health-care professionals dealing in menopause.